NATO airpower : organizing for uncertainty - Naslund, Willard E.; Project Air Force (U.S.). Strategy, Doctrine, and Force Structure Program; Rand Corporation; United States. Air Force (Santa Monica, CA : RAND, 1993)
In the future, NATO forces must be prepared to respond quickly to events in regions within and beyond its borders. This research addresses how this requirement will affect the organization of NATO forces, particularly airpower, by postulating two scenarios that would stress NATO to the extreme: (1) an attack by Russia on Poland, and (2) a Syria-Iraq attack on Turkey. The author uses these scenarios to develop operational concepts and alternative organizations that would enable NATO airpower to adapt to the uncertain post-Cold War environment. The report concludes that NATO's air reaction forces should be fully established in peacetime, prepared for operations independent from existing command structures, and that the future viability of these forces depends primarily on U.S. contributions.
"Project Air Force."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: North Atlantic Treaty Organization -- Armed Forces; Air defenses -- Europe; Air power -- Europe